KAPITA SELEKTA ILMU KOMUNIKASI (MEMAHAMI KOMUNIKASI SECARA TEORITIS DAN KONSEPTUAL) - Hendrawathy Putri, I Dewa Ayu (Institut Hindu Dharma Denpasar, 2018)
This approach to human communication consists of several key elements, such as; source or pengirtim message, send a message to the recipient who will receive the message. The recipient is the person who will interpret the message. Lasswell said that a good way to explain communication is to answer the following questions: Who Says What In The Channel To Whom With What Effect? Communication; is a social process in which individuals use symbols to create and interpret meanings in their environment. Verbal communication is a form of communication which is delivered orally or written using a language. Language is defined as a set of words structured so that it becomes a sentence that has meaning. Nonverbal communication is a collection of gestures, gestures, tone of voice, attitude, etc., which allows a person to communicate without words. Communication studies make someone sensitive to various strategies that can be used in various activities. Communication functions as an instrument to achieve personal and work goals, both short-term goals and long-term goals. Short-term goals for example to get praise, foster a good impression, gain sympathy, empathy, material, economic, and political benefits, which can be achieved among others by impression management, namely verbal and nonverbal tactics, such as speaking politely , sell promises, tastes in dress, etc. which are basically to show self-identity to others.